2019
DOI: 10.46792/fuoyejet.v4i1.246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Welding Power Input on the Microstructure and Impact Toughness of the Heat Affected Zone of 304L Austenitic Stainless Steel

Abstract: The effects of welding power input on the microstructural characteristics and impact behaviour of the Heat Affected Zone (HAZ) of type 304L austenitic stainless steel were investigated. This is with a view to optimize the welding process and ensure high weldment integrity of the heat affected zone.  Chemical analysis of the as-received 304L austenitic stainless steel was determined using an Optical Emission Spectrometry AR 4 30 metal analyzer. Thereafter, 30 samples of the as-received 304L austenitic stainless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Heat-affected zone HAZ is the most critical region in the welded joint. The micro-hardness of HAZ is majorly determined by the amount of WFR (determine the level of heat input) and TS (determine the level of cooling rate) [29]. When WFR increases, the level of heat input increases; higher heat input forms a coarse grain structure, resulting in a decline in microhardness.…”
Section: Base Metalmentioning
confidence: 99%
“…Heat-affected zone HAZ is the most critical region in the welded joint. The micro-hardness of HAZ is majorly determined by the amount of WFR (determine the level of heat input) and TS (determine the level of cooling rate) [29]. When WFR increases, the level of heat input increases; higher heat input forms a coarse grain structure, resulting in a decline in microhardness.…”
Section: Base Metalmentioning
confidence: 99%
“…The study's findings indicate that the specimens of AISI 316 stainless steel, which were welded using E316L-16 electrodes, demonstrated a greater joint efficiency than those welded using E312-17 electrodes. Further studies by [5] [13][14] also highlighted the significance of electrode selection in obtaining the required mechanical properties of welded joints.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the coating composition could influence the ageing stability of the weld metal. Oyetunji et al [16] studied the effect of welding process, type of electrode and electrode core diameter on the tensile strength of 304 ASS. They observed that the Ultimate Tensile Strength of the weld metal decreases with increasing core diameter of the electrode.…”
Section: Introductionmentioning
confidence: 99%